THE IMPACT OF TANGIBILITY, RELIABILITY AND RESPONSIVENESS ON THE OVERALL SATISFACTION OF THE CUSTOMERS - Shukri, Shakeerah Mohd; Yajid, Mohd Shukri Ab; Tham, Jacquline (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this work is to examine the impact of tangibility, reliability and responsiveness on the overall satisfaction of the customers in Malaysia. The data were gathered from the customer managers and customers and SPSS was used to check the reliability and hypotheses testing. The results indicated that positive nexus among the tangibility, reliability, responsiveness and overall satisfaction of the customers in Malaysia. These findings are helpful for the future researchers and policymakers that they should developed the policies that enhance the customer satisfaction in the country.